Decentralization and overborrowing in a fiscal federation - Si Guo; Yun Pei; Zoe Xie (Federal Reserve Bank of Atlanta, 2018)
We build an infinite horizon equilibrium model of fiscal federation, where anticipation of transfers from the central government creates incentives for local governments to overborrow. Absent commitment, the central government over-transfers, which distorts the central-local distribution of resources. Applying the model to fiscal decentralization, we find when decentralization widens local governments' fiscal gap, borrowings by both local and central governments rise. Quantitatively, fiscal decentralization accounts for from 19 percent to 40 percent of changes in general government debt in Spain during 1988-2006. A macroprudential tax on local borrowing that implements Pareto optimal allocation would reduce debt by 27 percent and raise welfare by 3.75 percent.
Keywords: E61; E62; H74; 330; fiscal federalism; time-consistent policy; decentralization; public debt